2015
DOI: 10.1007/s00394-015-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A causes p21 up-regulation in prostate cancer cells

Abstract: Our results indicate a potential role of UA as a chemopreventive agent for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Upon validation, a significant increase in anti-proliferative p21 mRNA and protein levels was observed. In addition, increased activity of the apoptotic enzymes, caspases 3 and 7 was seen (Sánchez-González et al, 2015). Other authors have also observed anti-apoptotic effects in other prostate cancer cells such as PC3 and DU 145, which are androgen independent, demonstrating that walnut polyphenols negatively affect prostate cancer cell viability via different mechanisms (Vicinanza et al, 2013).…”
Section: Prostatementioning
confidence: 82%
See 1 more Smart Citation
“…Upon validation, a significant increase in anti-proliferative p21 mRNA and protein levels was observed. In addition, increased activity of the apoptotic enzymes, caspases 3 and 7 was seen (Sánchez-González et al, 2015). Other authors have also observed anti-apoptotic effects in other prostate cancer cells such as PC3 and DU 145, which are androgen independent, demonstrating that walnut polyphenols negatively affect prostate cancer cell viability via different mechanisms (Vicinanza et al, 2013).…”
Section: Prostatementioning
confidence: 82%
“…Polyphenols have also been shown to act on multiple targets in pathways not only related to cellular proliferation and death (Fini et al, 2008), but also in inflammation (Kang et al, 2011), angiogenesis (Granci et al, 2010), and drug and radiation resistance (Garg et al, 2005). In particular, the effect walnut polyphenols have on cancer prevention has been studied widely, showing promising results (Spaccarotella et al, 2008;Reiter et al, 2013;Hardman, 2014;Sánchez-González et al, 2015). …”
Section: Metabolites Cancermentioning
confidence: 99%
“…Also, signaling molecules (Wnt/␤-catenin, EGFR) and key regulators of cell proliferation (p53, cMYC), cell cycle (cyclins), and apoptosis (caspases) are modified by urolithins in the cancer-responsive cells. Of interest, the induction of p21 has been confirmed in various colon and prostate cancer models, supporting this as a common mechanism of action underlying the ability of urolithins to blockage cell cycle and to inhibit cell proliferation [77,79,80]. To date, there are no animal studies specifically reporting the capacity of urolithins to moderate cancer development.…”
Section: Anticancer Effectsmentioning
confidence: 89%
“…They appear to act synergistically [33]. This supplement also increased the median lifespan of male mice [34]. However, one should be careful in controlling the doses of compounds and/or supplements that activate the Nrf2/ARE system.…”
Section: Introductionmentioning
confidence: 99%